#TITLE_ALTERNATIVE# - SOEKARTA , IDA
To obtain a pure chemical product, the presence of other unwanted elements should be avoided. These impurity elements may come from solvents, reagents or from the vessels being used. Glass vessels made from oxides of metal elements, can cause the presence-of the impurity.elements, due the low resistance of glass. Strong acids and bases may dissolve chemical elements of the glass vessels, indicating that the glass was not resistant to the influence of strong acids and bases. The resistance of glass can be expressed by the :increase of the amount of: metal ions in solution in terms of weight per unit surface area of the glass was attacked, In this work the resistance of soft glass and hard glass (pyrex was used) with respect to the influence of the strong acids HCl, HNO3 and the strong base, NaOH was determined. The content of metal ions in HC1, HN03 and NaOH was determined before and after heating in the glass vessels. Generaly, the result showed that HC1 had the lower ability to solve the metal elements of glasses than HNO3 or NaCH. It means that glass was more resistans towards the influence of HC1 than towards that of HNO3 or NaOH. The concentrations of HCl, HNO3 and NaOH used were 0,5 M, 1 M and 3 M, except in the analysis of K where 0.1 M, 0.2 M and 0.3 M of NaOH solution were used. As far as the duration of heating is concerned, abviouSly the longer the heating lasts the greater the concentration of metal ions found in solution, meaning that the glass resistance was decreasing more and more. In this work the heating lasted for f, 1 and 5 hours. To determine the concentration of metal ions in the solution the Atomic Absorbtion Spectrophotometric method was used. In this work the increase in the concentration of K, Na, Mg, Ca, Fe and Zn ions in solution was determined.